Index for Works of Arthur Colton : Hyperlinks to all Chapters in the Individual Ebooks - Colton, Arthur, 1868-1943; Widger, David, 1932-2021? (Salt Lake City, UT : Project Gutenberg, 2018)
"Index for Works of Arthur Colton" by Arthur Colton is a comprehensive compilation of various literary works authored by Colton, likely written during the late 19th to early 20th century. This collection spans multiple genres including novels, short stories, and narratives, illustrating themes that vary from adventure and exploration to philosophical reflections. It serves as a catalog of his contributions to literature, showcasing his versatility as a writer. The index contains titles such as "The Belted Seas," "The Debatable Land," and "Harps Hung Up in Babylon," each representing distinct narratives. For example, "The Belted Seas" follows the adventures of Captain Buckingham and explores his experiences at sea, while "The Debatable Land" delves into personal motivations and interactions between characters in a historical context. Other entries like "TIOBA, and Other Tales" and "The Cruise of the Violetta" highlight Colton's narrative style and thematic depth. Overall, this index not only lists Colton's works but also provides a glimpse into the diverse storytelling and philosophical explorations he engaged with throughout his writing career. (This is an automatically generated summary.)
Release date is 2018-07-10
Produced by David Widger
Keywords: Indexes